Asylum v. sovereignty in the 21st century: how nation-states breach international law to block access to asylum. (2016) - Campbell, John R.
Asylum was created by the international community in the 20th century to provide humanitarian protection to individuals fleeing persecution by nation states, but the ability to obtain asylum has been fundamentally reshaped by sovereign national interests in the 21st century. I look at asylum policy and practice in the UK, and secondarily the European Union, to examine two key areas where state policy is in tension with a state's international legal obligations. I first explore policies which nation-states have adopted to prevent asylum seekers from gaining access to their territory, which criminalise those who enter a country of asylum and frustrate their ability to obtain asylum. Arguably restrictive state policies breach international law, which raises questions regarding whether a state can be made to comply with its international legal obligations. I explore this issue by looking at how UNHCR has exercised its 'supervisory role' over the UK. I conclude that UNHCRs interventions are not able to ensure that a state honours and complies with its international legal obligations, which necessarily means that asylum-seekers will find it increasingly difficult to secure protection.